When women kill - Mann, Coramae Richey, 1931- (SUNY series in violence., 1996)
The volume explores every aspect of females who murdered - from arrest through sentencing - and provides descriptions of ecological and other circumstances of the murders, the victims, the motives of the perpetrators, and their fates in court. The generous utilization of case examples dramatically reveals three homicide scenarios. This exploratory, descriptive study compares 296 females arrested for homicide in six urban areas - Atlanta, Baltimore, Chicago, Houston, Los Angeles, and New York City in 1979 and 1983. During field trips to these cities, which have the highest murder rates in the country, both qualitative and quantitative data were collected from police files, homicide records, FBI reports, and criminal information. Research analyses reveals a fascinating profile of today's female murderer. When Women Kill presents a comprehensive, yet highly readable, overview of this previously neglected subgroup of homicide offenders.